Beat the heat: Culex quinquefasciatus regulates its body temperature during blood feeding. (February 2021) - Reinhold, Joanna M.; Shaw, Ryan; Lahondère, Chloé
Abstract: Mosquitoes are regarded as one of the most dangerous animals on earth. Because they are responsible for the spread of a wide range of both human and animal pathogens, research of the underlying mechanisms of their feeding behavior and physiology is critical. Among disease vector mosquitoes, Culex quinquefasciatus, a known carrier of West Nile virus and Western Equine Encephalitis, remains relatively understudied. As blood-sucking insects, adaptations (either at the molecular or physiological level) while feeding on warm blood are crucial to their survival, as overheating can result in death due to heat stress. Our research aims to determine how Cx. quinquefasciatus copes with the heat associated with warm blood meal ingestion and possibly uncover the adaptations this species uses to avoid thermal stress. Through the use of thermographic imaging, we analyzed the body temperature of Cx. quinquefasciatus while blood feeding. Infrared thermography has allowed us to identify a cooling strategy, evaporative cooling via the production of fluid droplets, and an overall low body temperature in comparison to the blood temperature during feeding. Understanding Cx. quinquefasciatus' adaptations and the strategies they employ to reduce their body temperature while blood feeding constitutes the first step towards discovering potential targets that could be used for their control. Highlights: Mosquitoes have evolved adaptations to cope with heat stress associated with warm blood ingestion. Culex quinquefasciatus displays heterothermy while blood-feeding. Retention of urine droplets decreased abdominal temperatures via evaporative cooling. Overall, during blood-feeding, the mosquito body temperature is much cooler than the ingested blood.